ALGORITMA PRIM DALAM PENENTUAN LINTASAN TERPENDEK DAN LINTASAN TERCEPAT PADA PENDISTRIBUSIAN BARANG PT.SUMBER ALFARIA TRIJAYA TBK PEKANBARU - hana rezki yana; depriwana rahmi; annisah kurniati; suci yuniati (Matematika Sains, 2024)
distribution of goods PT Sumber Alfaria Trijaya Tbk Pekanbaru by using Prim's Algorithm. Data and information that includes all paths connecting alfamart-alfamart are obtained through the google maps application. Mini data is used to build an initial model in the form of a connected weighted graph. By using Prim's Algorithm, optimization of the path model is carried out, so that the minimum spanning tree is obtained. Based on this minimum spanning tree, the shortest path and the fastest path from PT.Sumber Alfaria Trijaya are 25.5 km and 50 minutes, respectively.